Presentation of a diagnostically challenging case of chronic eosinophilic leukemia with marrow dysplasia and ringed sideroblasts. (December 2020) - Vormittag-Nocito, Erica; Khan, Irum; Wiley, Elizabeth; Behm, Frederick; Ni, Hongyu
Chronic eosinophilic leukemia, not otherwise specified can be challenging to differentiate from hypereosinophilic syndrome and myelodysplastic syndromes with elevated eosinophilia. We present a diagnostically challenging case of chronic eosinophilic leukemia, not otherwise specified that initially seemed like a myelodysplastic syndrome but progressed to eosinophilic tissue infiltration and overt eosinophilic dyspoiesis. In addition, we discuss the morphologic and molecular findings that can overlap among these entities that made the diagnosis difficult in the case presented.